Examination of Metoprolol Pharmacokinetics and Pharmacodynamics Across CYP2D6 Genotype‐Derived Activity Scores. (3rd November 2020) - Thomas, Cameron D.; Mosley, Scott A.; Kim, Sarah; Lingineni, Karthik; El Rouby, Nihal; Langaee, Taimour Y.; Gong, Yan; Wang, Danxin; Schmidt, Siegfried O.; Binkley, Philip F.; Estores, David S.; Feng, Kairui; et al.
Abstract : Recent CYP2D6 phenotype standardization efforts by CYP2D6 activity score (AS) are based on limited pharmacokinetic (PK) and pharmacodynamic (PD) data. Using data from two independent clinical trials of metoprolol, we compared metoprolol PK and PD across CYP2D6 AS with the goal of determining whether the PK and PD data support the new phenotype classification. S‐metoprolol apparent oral clearance (CLo), adjusted for clinical factors, was correlated with CYP2D6 AS ( P  < 0.001). The natural log of CLo was lower with an AS of 1 (7.6 ± 0.4 mL/minute) vs. 2–2.25 (8.3 ± 0.6 mL/minute; P  = 0.012), similar between an AS of 1 and 1.25–1.5 (7.8 ± 0.5 mL/minute; P  = 0.702), and lower with an AS of 1.25–1.5 vs. 2–2.25 ( P =  0.03). There was also a greater reduction in heart rate with metoprolol among study participants with AS of 1 (−10.8 ± 5.5) vs. 2–2.25 (−7.1 ± 5.6; P  < 0.001) and no significant difference between those with an AS of 1 and 1.25–1.5 (−9.2 ± 4.7; P =  0.095). These data highlight linear trends among CYP2D6 AS and metoprolol PK and PD, but inconsistencies with the phenotypes assigned by AS based on the current standards. Overall, this case study with metoprolol suggests that utilizing CYP2D6 AS, instead of collapsing AS into phenotype categories, may be the most precise approach for utilizing CYP2D6 pharmacogenomics in clinical practice.